2020
DOI: 10.3389/fmars.2020.566021
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding for the Assessment of the Taxonomy and Conservation Status of the Fish Bycatch of the Northern Brazilian Shrimp Trawl Fishery

Abstract: Trawling is a controversial fishing method due to the perceived lack of selectivity of the net and the resulting capture of a large quantity and diversity of non-target species. Here, we used DNA barcode methods to identify the composition of the bycatch produced by the trawl fishery of the Brazilian North coast. A total of 182 species belonging to 18 orders and 62 families were captured, including 17 species under some degree of threat in the wild according to the IUCN Red List of Threatened Species (IUCN). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The integration of morphological and molecular taxonomic approaches carried out in the present work provides a further confirmation of the appropriateness of integrated methods for the identification of copepods, as demonstrated also for other organisms (Fontaneto et al, 2015;Avó et al, 2017;Mills et al, 2017;Guimarães-Costa et al, 2020). The success of using barcoding for single-species identification depends on the presence of high-quality reference data available in public sequence libraries (Bucklin et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…The integration of morphological and molecular taxonomic approaches carried out in the present work provides a further confirmation of the appropriateness of integrated methods for the identification of copepods, as demonstrated also for other organisms (Fontaneto et al, 2015;Avó et al, 2017;Mills et al, 2017;Guimarães-Costa et al, 2020). The success of using barcoding for single-species identification depends on the presence of high-quality reference data available in public sequence libraries (Bucklin et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…(Marceniuk et al, 2019). Similarly, molecular data identified Narcine brasiliensis and Mustelus canis (Guimarães-Costa et al, 2020;Rodrigues-Filho et al, 2020) while integrative analyses based on morphological, genetic and ecological studies recorded H. berthalutzae (Pentean et al, 2020) for this region. These data highlight the importance of focusing on the diversity of elasmobranchs in the north coast of Brazil, as recent studies have identified distinct results on the species composition in this group of fishes.…”
Section: Diversity Of Elasmobranchs In the Amazon Coastmentioning
confidence: 84%
“…A potential obstacle to a proper identification of the species was the lack of whole specimens to be used as a voucher for morphological identification as well as the absence of sequences in public datasets for comparative analyses (Rodrigues-Filho et al, 2020). In recent years, studies based on molecular identification of stingray species have allowed both the identification of valid species and the registration of new occurrences and new species (Guimarães-Costa et al, 2020;Pentean et al, 2020). In a recent study, Rodrigues-Filho et al ( 2020) identified nine ray species on the Amazon coast using DNA barcodes.…”
Section: Diversity Of Elasmobranchs In the Amazon Coastmentioning
confidence: 99%
See 1 more Smart Citation
“…In the decades since a DNA barcoding system for specimen identifications was established, numerous studies have proven that this technique is effective for identifying species (Hajibabaei et al, 2006;Ward et al, 2009;Radulovici et al, 2010). DNA barcoding has now been successfully applied in insects (Janzen et al, 2005;Smith et al, 2005), crustaceans (Costa et al, 2007;Bilgin et al, 2014;Bucklin et al, 2022), fish (Ward et al, 2005;Hubert et al, 2008;Ghouri et al, 2020;Guimarães-Costa et al, 2020;Xu et al, 2021), birds (Hebert et al, 2004), and mammals (Lorenz et al, 2005;Clare et al, 2007). These achievements have benefited from the establishment of the Barcode of Life Data Systems (BOLDSystems), which is a global public standard dataset platform with general technical rules and identification systems for animal taxonomy.…”
Section: Introductionmentioning
confidence: 99%